Radiation segmentectomy for curative intent of unresectable very early to early stage hepatocellular carcinoma (RASER): a single-centre, single-arm study. (September 2022) - Kim, Edward; Sher, Alex; Abboud, Ghadi; Schwartz, Myron; Facciuto, Marcelo; Tabrizian, Parissa; Knešaurek, Karin; Fischman, Aaron; Patel, Rahul; Nowakowski, Scott; Llovet, Josep; Taouli, Bachir; et al.
Summary: Background: Unresectable solitary very early to early stage hepatocellular carcinoma is managed with ablation for curative intent. Radiation segmentectomy is a treatment option that delivers radioactive 90 yttrium ( 90 Y)-bound microspheres transarterially to a segment of liver. The aim of this study was to assess the safety and efficacy of radiation segmentectomy in patients with unresectable hepatocellular carcinoma deemed unfavourable for ablation. Methods: RASER was a single-centre, single-arm study that included adults (>18 years) with solitary hepatocellular carcinoma with unfavourable location for ablation, without metastasis or macrovascular invasion. Eligibility criteria included measurable disease 3 cm or less in diameter, Child-Pugh score A–B7, an Eastern Cooperative Oncology Group score of 0, and adequate haematological and organ function. The primary endpoint was target tumour response measured by mRECIST. Patients were followed up with imaging and office visits for up to 24 months. The trial is registered with ClinicalTrials.gov (NCT03248375 ), and is completed. Findings: Individuals were enrolled between Aug 3, 2016, and April 4, 2019, and the last patient follow-up occurred on March 31, 2021. Of the 44 individuals assessed for eligibility, 29 patients were included in the study. Initial target lesion complete response was observed in 24 (83%) of 29 patients, and partial response was observed in five (17%) of patients. All patients had an initial objective response and 26 (90%) individuals had a sustained complete response. Four (14%) patients had grade 3 leukopenia and two (7%) had grade 3 thrombocytopenia. There were two (7%) non-laboratory-related grade 3 adverse events (one arterial injury and one ascites). The most frequent (>10% patients) grade 1 or 2 adverse events were fatigue (nine [31%]); nausea, vomiting, or anorexia (seven [24%]); abdominal discomfort (six [21%]), leukopenia (nine [31%]), thrombocytopenia (four [14%]), increased alkaline phosphatase (four [14%]), increased alanine or aspartate aminotransferase (four [14%]), increased bilirubin (four [14%]), and decreased albumin (six [21%]). There was one death that was not treatment related. Interpretation: Radiation segmentectomy was efficacious, with a low proportion of high-grade adverse events in patients with unresectable very early to early stage hepatocellular carcinoma with suboptimal location for ablation. These results suggest that radiation segmentectomy should be further investigated as a potential curative treatment option for well selected patients. Funding: Boston Scientific.